ChemInform Abstract: Dipotassium Diaquadiphosphatooctaperoxotetramolybdate, [K2(P2O7)MoO (O2)22 MoO(O2)2(OH2)2]2‐ — A One‐Dimensional Double Chain Array of Polyanions linked by Potassium Cations. Issue 47 (4th November 2013) - Aoki, Koji; Iwata, Keisuke; Iwata, Takahiro; Hashimoto, Masato
Abstract The title anion is synthesized by reaction of metallic molybdenum dissolved in H2O2, K4P2O7 and Me4NCl (H2O, 20 °C, 1—2 d; 69% yield).